Pengaruh Buy Back Saham terhadap Kinerja Keuangan dan Kinerja Pasar (Studi Kasus PT. Bakrie Sumatera Plantations Tbk.) - Oktavius Samsurya Kadang (Jurnal Riset Manajemen dan Bisnis, 2008)
This research aimed at understanding the influence of, the stock bryback on the performances of finance ond mwket of PT Babie sumatera plontatiorc.  This research used the quarterly finance data of the company abtained from the official website of the Indonesia stock hchange @EI) andfrom the daily stock price retriarcdfrom Yahoo Finance. The research periods were the third quffiter of 20A8, thefowth quwtu of 2008, andthefirst quoter of 2009. The ratio analysis result using trend concluded that A the time of doins the buyback, the finance performonce declined because of the *tng if the ratio of the debt and thefalli4g of the ratio of the liquidity. afier uecatiig uryback, the eompany liquidity ratio decreased and the debt ratio increasecl,whereas the ratio of RoA, RoE, and EPS was getting better because of the efrciency of the company. The mtket performance, whichwas anallzed based on the 6)erage of the stock price quarterly, deereased by the time of buyback"whereas arter doing the buybacli, the paform(mce was getting better aithough the *ternalfactors of the comp@ry was stronger in supporting the stockpriie.Keywords: Stock buybac\ financial ratio, performorce of finance,performance ofmmket.